Sectoral Market Sensitivities to Macroeconomic Signals and Global Moderators in a Digitally Shifting Investment Landscape - Fikriyah, Nabillah Fauziatul; Yuliana, Indah (Journal of Social Commerce, 2025)
This paper will look into the effects of rupiah exchange rate, inflation and interest rates on the composite stock price index (IHSG), as well as the nine sectoral indices in the Indonesian financial market. Since the behavior of the market is being increasingly defined by wider systemic factors, the analysis introduces the money supply and the Dow Jones Industrial Average (DJIA) index; which acts as moderating variables; that either alleviates or reduces the extent or orientation of these macroeconomic relationships. The quantitative study design was selected that implies the use of multiple regression and Moderated Regression Analysis (MRA) with monthly data collected in the period between January 2019 and December 2023. The findings show that the macroeconomic variations are not evenly spread in all sectors. The inflationary pressure and exchange rate changes are sector specific whereas interest rate movements mostly put pressure on the downward side particularly in capital-intensive sectors. The tempering influence of liquidity and international sentiment is also created to be highly considerable showing that the receiving of a macroeconomic message is not only a factor of investor response but also a factor of the interpretive condition under which it is conveyed.